2022
DOI: 10.1039/d2ra04128f
|View full text |Cite
|
Sign up to set email alerts
|

Direct selenosulfonylation of unsaturated compounds: a review

Abstract: In this review, we have discussed recent developments on the direct selenosulfonylation of unsaturated compounds which lead to the formation of two new carbon-sulfur and carbon-selenium bonds in a single operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…Existing reviews [6] mainly focused on one specified kind of reaction or what products can be obtained. For example, in 2022, Azime and co‐workers [6a] has reviewed the selenosulfonylation of alkenes. They mainly discussed the synthesis of β‐ selenosulfones.…”
Section: Selenylationmentioning
confidence: 99%
“…Existing reviews [6] mainly focused on one specified kind of reaction or what products can be obtained. For example, in 2022, Azime and co‐workers [6a] has reviewed the selenosulfonylation of alkenes. They mainly discussed the synthesis of β‐ selenosulfones.…”
Section: Selenylationmentioning
confidence: 99%
“…Addition reactions, especially via double functionalization of unsaturated compounds, have also been broadly applied for the synthesis of chalcogen-bearing compounds. 25,[48][49][50][51][52][53][54][55][56] However, complicated chemo-, regio-and stereoselective issues exist under certain circumstances. Over the past two decades, the direct chalcogenation of C-H bonds has evolved as a straightforward, atom-and step-economical method for the preparation of chalcogenated compounds including organyl sulfides, selenides, sulfones, trifluoromethylthioethers, thiocyanates and selenocyanates.…”
Section: Introductionmentioning
confidence: 99%
“…These existing approaches are restricted to the addition of aryl sulfones, the presynthesis of enamide substrates, and multistep reactions. Nowadays, intermolecular regioselective 1,2-difunctionalization of alkynes is a potent tool for upgrading feedstocks into molecules because it permits the simultaneous installation of two vicinal new bonds. Several approaches including hydrosulfonylation, aminosulfonylation, carbosulfonylation, oxysulfonylation, thiosulfonylation, seleno-sulfonylation, and halosulfonylation have been developed for the synthesis of these sulfonylated compounds. In 2017, Bi et al reported an intermolecular radical reaction using silver catalyst for the synthesis of aminosulfonylation of alkynes (Scheme b) .…”
Section: Introductionmentioning
confidence: 99%